ECONOMETRIC MODELS IN RESEARCHING THE IMPACT OF SPORT INDUSTRY ON SOCIAL AND ECONOMIC DEVELOPMENT OF THE REGION (illustrated by the Republic of Mordovia) - Elena V. Zarova; Il'ya V. Solntsev (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article offers a critical analysis of overseas and home research dealing with the impact of physical culture and sports and arrangement of big sport events on economic and social development of the country. It is pointed out that special attention in them is paid to designing and testing methods of investigating the factors, which ensure sport achievements of the country. But at the same time methods of quantitative analysis of the impact which sport industry development has on economic and social parameters of the region have not been studied in theoretical and applied aspects. Research in this directions is especially acute for countries which carry out big sports events. The efficiency of sport industry entities influences the development of national and regional social and economic systems, shapes their economic potential and investment appeal. The author's methodology of statistic analysis and designing econometric models of the impact of sport industry development on figures of social and economic development of the region was shown using the example of the Republic of Mordovia - entity of the Russian Federation, which takes high positions in the rating of people involvement in physical culture and sports and arranges many big sports events. The article also puts forward the suggestions for using the methodology in practical administration of the region.